Words, borders, herds: postsocialist English and nationalist language identities in Mongolia - Marzluf, Phillip P. (My University, 2012)
This article focuses on the sociolinguistics of globalism (Blommaert 2010) in Mongolia by examining two dominant language identities, postsocialist English and fundamentalist nationalist Mongolian. Postsocialist English, emerging as a vital part of the free-market capitalist economy in the 1990s, is analyzed in relationship with the now receding language identity of socialist Russian. Postsocialist English supports the values of transnational development, neoliberal economic policies, and post-industrial educational practices. The Mongolian fundamentalist nationalist language identity, on the other hand, responds to free-market globalism by appeals to the land and the traditional pastoral economy of herding. Yet, despite the fact that postsocialist English identifies Mongolians with anti-traditional and urban cultural and social values, the fundamentalist nationalist identity does not perceive of English as a threat; in fact, postsocialist English is used to mediate the anxiety that nationalist Mongolians feel towards China and their other new Asian trading partners. As free-market globalism continues to transform postsocialist Mongolia, including urban migration and the industrial mining of coal and other raw minerals, a sociolinguistics of globalism can continue to navigate the ways in which Mongolians craft their identity through language and, especially, the ways it relates to traditional notions of the land and the pastoral economy.
Keywords: Mongolia; Globalism; Postsocialism; Nationalism; World English